A Challenging Case of Leptospirosis - Leite, Ana Bento; Santos, Raquel; Maia, Mariana (Brazilian Journal of Case Reports, 2025)
Leptospirosis is a significant zoonosis caused by the pathogenic bacterium Leptospira, which is transmitted directly or indirectly from animals to humans. It is a potentially severe but treatable disease. Its symptoms may mimic those of other infections, such as rickettsiosis, influenza, meningitis, or hepatitis. The disease spectrum ranges from subclinical infection to severe multi-organ failure with high mortality. Diagnosis is usually made through serology. However, a key limitation of serological testing is that antibodies are absent during the acute phase. In the early days of illness, the only sensitive and specific test is polymerase chain reaction (PCR). In Portugal, leptospirosis has gained increasing importance and is a notifiable disease. The authors present the case of a farmer with fever, headache, and rash who progressed to pancytopenia and hepatic cholestasis. A positive real-time PCR in a blood sample, specific for Leptospira, confirmed the diagnosis in the acute phase of the disease before antibody titers became detectable. Leptospira serologies remained negative. After antibiotic therapy and supportive care, the patient showed favorable clinical progression. Early diagnosis prevented complications. The authors report a challenging case of leptospirosis and aim to raise awareness about the importance of early diagnosis and appropriate treatment. Occupational exposure is a significant risk factor. Public health alert systems are essential to reduce risk. The need for rapid diagnosis at admission has driven the development of various PCR assays, which carry economic implications. Their advantage lies in confirming the diagnosis during the acute phase of disease, before antibody detection, and they may support improved public health control measures. However, molecular tests are still unavailable in some areas.